THE EFFECTIVENESS OF THE RADEC LEARNING MODEL IN ENHANCING FIFTH-GRADE STUDENTS’ READING COMPREHENSION SKILLS OF PROCEDURAL TEXTS - Hilma Mustika Fauziyyah; Prana Dwija Iswara; Wahyu Sopandi (Universitas Majalengka, 2025)
This study aims to examine the effectiveness of the RADEC (Read-Answer-Discuss-explain-Create) learning model in improving fifth-grade elementary students’ reading comprehension of procedural texts compared to conventional instruction. A quasi-experimental design with a non-equivalent group pretest-posttest method was applied. The participants consisted of fifth-grade students from two elementary schools in Kuningan Regency, divided into experimental and control groups. Data were collected through pretest and posttest, then analyzed using an independent sample t-test assisted by Jeffreys’s Amazing Statictics Program (JASP). The results showed a statistically significant difference in improvement between the two goups, as indicated by a p-value of 0.001 (sig. 2-tailed< 0.05). These findings suggest that the RADEC model is effective in enhancing students’ reading comprehension, especially in understanding procedural texts, when compared to conventional learning. The implication of this research is that the RADEC learning model has the potential to be adopted as an innovative learning model to support literacy development at the elementary school level.